Ambient temperature and infarct size, microvascular obstruction, left ventricular function and clinical outcomes after ST-segment elevation myocardial infarction. Issue 2 (March 2022) - Redfors, Björn; Simonato, Matheus; Chen, Shmuel; Vincent, Flavien; Zhang, Zixuan; Thiele, Holger; Eitel, Ingo; Patel, Manesh R.; Ohman, E. Magnus; Maehara, Akiko; Ben-Yehuda, Ori; Stone, Gregg W.
Abstract : Objectives: Incidence and prognosis of ST-segment elevation myocardial infarction (STEMI) vary according to ambient temperature and season. We sought to assess whether season and temperature on the day of STEMI are associated with infarct size, microvascular obstruction (MVO), left ventricular ejection fraction (LVEF) and clinical outcomes after primary percutaneous coronary intervention (PCI). Methods: Individual patient data from 1598 patients undergoing primary PCI in six randomized clinical trials were pooled. Infarct size was evaluated by cardiac magnetic resonance within 30 days in all trials. Patients were categorized either by whether they presented on a day of temperature extremes (minimum temperature <0 °C or maximum temperature >25 °C) or according to season. Results: A total of 558/1598 (34.9%) patients presented with STEMI on a day of temperature extremes, and 395 (24.7%), 374 (23.4%), 481 (30.1%) and 348 (21.8%) presented in the spring, summer, fall and winter. After multivariable adjustment, temperature extremes were independently associated with larger infarct size (adjusted difference 2.8%; 95% CI, 1.3–4.3; P  < 0.001) and smaller LVEF (adjusted difference −2.3%; 95% CI, −3.5 to −1.1; P  = 0.0002) but not with MVO (adjusted P  = 0.12). In contrast, infarct size, MVO and LVEF were unrelated to season (adjusted P  = 0.67; P  = 0.36 and P  = 0.95, respectively). Neither temperature extremes nor season were independently associated with 1-year risk of death or heart failure hospitalization (adjusted P  = 0.79 and P  = 0.90, respectively). Conclusion: STEMI presentation during temperature extremes was independently associated with larger infarct size and lower LVEF but not with MVO after primary PCI, whereas season was unrelated to infarct severity. Abstract : Supplemental Digital Content is available in the text.